The Impact of Dietary Habits and Maternal Body Composition on Human Milk Microbiota—Polish Pilot Study - Agnieszka Bzikowska-Jura; Anna Koryszewska-Bagińska; Małgorzata Konieczna; Jan Gawor; Robert Gromadka; Aleksandra Wesołowska; Gabriela Olędzka (Molecules, 2025)
Human milk (HM) is a complex biological fluid that plays a significant role in infant health, influenced by maternal dietary habits and body composition. This study aimed to explore how maternal diet and nutritional status affect the microbial composition of HM. In this pilot study, 15 mothers were recruited from a maternity ward and assessed for dietary habits through a semi-structured food frequency questionnaire and a 3-day dietary record. Maternal body composition was evaluated using bioelectrical impedance analysis. HM samples were collected for microbiota analysis, focusing on the diversity and composition of bacterial communities via 16S rRNA sequencing. The study identified that maternal nutrient intake significantly correlated with the composition of HM microbiota. Specifically, Firmicutes abundance showed positive correlations with animal protein (τ = 0.39; p = 0.043), total carbohydrates (τ = 0.39; p = 0.043), and vitamin A (τ = 0.429; p = 0.026). Bacteroidota was positively correlated with retinol (τ = 0.39; p = 0.043). Higher consumption of dietary fiber (>24 g/day) did not yield significant differences in bacterial composition compared to lower intake (<24 g/day) (p = 0.8977). Additionally, no significant differences were found in overall bacterial abundance across different maternal characteristics such as age, mode of delivery, or breastfeeding type. This study underscores the importance of maternal diet in shaping the HM microbiota, which may have implications for infant health. Dietary modifications during lactation could be a strategic approach to promote beneficial microbial colonization in HM. Further research is warranted to confirm these findings and explore the underlying mechanisms.